Management Psychology in Educational Organizations: A Systematic Literature Review of Motivation, Communication, and Well-Being as Determinants of School Effectiveness - Nur Faizah Zulfa; Nur Fika Anjani; Haidar Rafli Rasyad; Mu’alimin Mu’alimin (Responsive: Jurnal Manajemen Pendidikan Islam, 2026)
The increasingly complex development of educational organizations demands the integration of managerial approaches and psychological aspects in their management. Management psychology is important because it plays a role in understanding motivation, communication, leadership, and human resource well-being, which have a direct impact on the effectiveness of educational institutions. This article aims to analyze and synthesize research trends in management psychology in the educational context over the past five years and identify the dominant dimensions that contribute to improving organizational performance. The research questions focus on: (1) what are the trends and main focuses of management psychology studies in education; and (2) what dimensions are most dominant in improving the effectiveness of educational organizations. This study uses a systematic literature review approach through the Google Scholar database with the help of the Publish or Perish application using the keywords "management psychology," "educational organizations," "teacher motivation," and "organizational communication." From the initial 50 identified articles, five main articles were selected for in-depth analysis. The results of the study indicate three dominant themes: motivation and school effectiveness, organizational communication and teacher performance, and well-being and stress management. Overall, management psychology contributes significantly to improving the quality and sustainability of educational organizations. Further research is recommended to use a quantitative approach, mixed methods, or meta-analysis and integrate a digital transformation perspective.